EMOTIONAL AND EXPRESSIVE IMPACT FEATURES OF ABBREVIATED UNITS IN ENGLISH AND UZBEK LANGUAGES (American Journal of Pedagogical and Educational Research, 2026)
This article analyzes the emotional and expressive potential of abbreviated units in English and Uzbek. The study examines the pragmatic functions of abbreviations (abbreviations, acronyms, and initialisms) in speech, their communicative effectiveness, and their stylistic load. The results show that in both languages, abbreviations serve not only to convey information concisely but also to enliven speech, add emotional coloring, and influence the audience.